Sublingual Delivery of Astaxanthin through a Novel Ascorbyl Palmitate-Based Nanoemulsion: Preliminary Data - Andrea Fratter; Damiano Biagi; Arrigo F. G. Cicero (Marine Drugs, 2019)
Astaxanthin is a carotenoid extracted from several seaweeds with ascertained therapeutic activity. With specific reference, astaxanthin is widely used in clinical practice to improve ocular tissue health and skin protection from UV ray damages. Despite its well-documented pleiotropic actions and demonstrated clinical efficacy, its bioavailability in humans is low and limited because of its hydrophobicity and poor dissolution in enteric fluids. Furthermore, astaxanthin is very unstable molecule and very sensitive to light exposure and thermal stress. Taken together, these pharmacological and chemical−physical features strongly limit pharmaceutical and nutraceutical development of astaxanthin-based products and as a consequence its full clinical usage. This work describes the preliminary in vitro investigation of sublingual absorption of astaxanthin through a novel ascorbyl palmitate (ASP) based nanoemulsion.